2019
DOI: 10.1177/0921374019826200
|View full text |Cite
|
Sign up to set email alerts
|

Water is life, but the colony is a necropolis: Environmental terrains of struggle in Puerto Rico

Abstract: The catastrophic conditions after Hurricane Maria in Puerto Rico, homeland to the second largest US Latinx group, also result from a long history of colonial exploitation exacerbated by economic downturn, debt crisis, and federally imposed austerity. US policies affecting agriculture and attracting contaminating industries set the groundwork for extreme environmental degradation, which in turn has long motivated local community activism, coalition-building, and de-colonial praxis. The authors illustrate that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
(60 reference statements)
0
13
0
Order By: Relevance
“…The cultural and educational programming previously sponsored by the ELA was far from sustainable, as seen in drastic budget cuts to agencies such as the Institute of Puerto Rican Culture, the headquarters for which is now slated to become a hotel (Meléndez García 2019); the public television network WIPR, which is up for privatization (Hernández Mercado 2020); and the public school system, battered by the closure of more than four hundred schools, which is roughly a third of the schools Puerto Rico had before 2016 (Brusi 2020). With the declaration of the debt crisis in 2016, this debilitated cultural apparatus began to collapse, along with local roadways, the electric grid, and other forms of infrastructure, thus making undeniable Puerto Rico's colonial status and subordinate racial position (Ficek 2018;Lloréns and Stanchich 2019).…”
Section: Historical Context: the Rise And Fall Of The Puerto Rican Racial Statementioning
confidence: 99%
“…The cultural and educational programming previously sponsored by the ELA was far from sustainable, as seen in drastic budget cuts to agencies such as the Institute of Puerto Rican Culture, the headquarters for which is now slated to become a hotel (Meléndez García 2019); the public television network WIPR, which is up for privatization (Hernández Mercado 2020); and the public school system, battered by the closure of more than four hundred schools, which is roughly a third of the schools Puerto Rico had before 2016 (Brusi 2020). With the declaration of the debt crisis in 2016, this debilitated cultural apparatus began to collapse, along with local roadways, the electric grid, and other forms of infrastructure, thus making undeniable Puerto Rico's colonial status and subordinate racial position (Ficek 2018;Lloréns and Stanchich 2019).…”
Section: Historical Context: the Rise And Fall Of The Puerto Rican Racial Statementioning
confidence: 99%
“…The water system was also in crisis. A report from May of 2017 showed that 70% of the island's drinking water was possibly toxic (Llor� ens & Stanchich, 2019;Cotto, 2017). A report on the hospital system had also tried to sound the alarm about the inability of the health system to respond in case of a crisis (Gonz� alez, 2018).…”
Section: Servicingmentioning
confidence: 99%
“…Most Hurricane-related deaths are attributed to infrastructural failure and inadequate responses to the crisis, both of which are implicated in the long history of ruinous governance which placed older people and people living in poverty at greatest risk (Holpuch 2018;Milken Institute 2018). Infrastructural failure reflects the fact that rapid industrialization was prioritized in the 1950s, without taking into account the futures of those on the island (Lloréns and Stanchich, 2019). Lloréns and Stanchich (2019) note that the interests of global capitalism and the accumulation of wealth for non-residents have been facilitated at the expense of the people on the island.…”
Section: Puerto Rico-united States Entanglements and Citizenship As Imperial Debrismentioning
confidence: 99%
“…Infrastructural failure reflects the fact that rapid industrialization was prioritized in the 1950s, without taking into account the futures of those on the island (Lloréns and Stanchich, 2019). Lloréns and Stanchich (2019) note that the interests of global capitalism and the accumulation of wealth for non-residents have been facilitated at the expense of the people on the island. Simultaneously Molina-Guzmán (2019) points out the Jones Act and the control it grants the US military over Puerto Rico's coasts and waters prevented international aid from reaching Puerto Rico after Hurricane Maria.…”
Section: Puerto Rico-united States Entanglements and Citizenship As Imperial Debrismentioning
confidence: 99%